Protein kinase C (PKC) participates in acetaminophen hepatotoxicity through c‐jun‐N‐terminal kinase (JNK)‐dependent and ‐independent signaling pathways. Issue 4 (3rd March 2014) - Saberi, Behnam; Ybanez, Maria D.; Johnson, Heather S.; Gaarde, William A.; Han, Derick; Kaplowitz, Neil
<x xml:space="preserve">Abstract</x> This study examines the role of protein kinase C (PKC) and AMP‐activated kinase (AMPK) in acetaminophen (APAP) hepatotoxicity. Treatment of primary mouse hepatocytes with broad‐spectrum PKC inhibitors (Ro‐31‐8245, Go6983), protected against APAP cytotoxicity despite sustained c‐jun‐N‐terminal kinase (JNK) activation. Broad‐spectrum PKC inhibitor treatment enhanced p‐AMPK levels and AMPK regulated survival‐energy pathways including autophagy. AMPK inhibition by compound C or activation using an AMPK activator oppositely modulated APAP cytotoxicity, suggesting that p‐AMPK and AMPK regulated energy survival pathways, particularly autophagy, play a critical role in APAP cytotoxicity. Ro‐31‐8245 treatment in mice up‐regulated p‐AMPK levels, increased autophagy (i.e., increased LC3‐II formation, p62 degradation), and protected against APAP‐induced liver injury, even in the presence of sustained JNK activation and translocation to mitochondria. In contrast, treatment of hepatocytes with a classical PKC inhibitor (Go6976) protected against APAP by inhibiting JNK activation. Knockdown of PKC‐α using antisense (ASO) in mice also protected against APAP‐induced liver injury by inhibiting JNK activation. APAP treatment resulted in PKC‐α translocation to mitochondria and phosphorylation of mitochondrial PKC substrates. JNK 1 and 2 silencing in vivo decreased APAP‐induced PKC‐α translocation to mitochondria, suggesting PKC‐α and JNK interplay in a feed‐forward mechanism to mediate APAP‐induced liver injury. Conclusion: PKC‐α and other PKC(s) regulate death (JNK) and survival (AMPK) proteins, to modulate APAP‐induced liver injury. (Hepatology 2014;59:1543‐1554)